Antibiotic prophylaxis for ERCP: a randomized clinical trial comparing ciprofloxacin and cefuroxime in 200 patients at high risk of cholangitis. - Mehal, W; Culshaw, K; Tillotson, G; Chapman, R (1995)
OBJECTIVE: To compare the efficacy and safety of oral ciprofloxacin and intravenous cefuroxime in patients at high risk of cholangitis after endoscopic retrograde cholangiopancreatography (ERCP). DESIGN: Prospective, randomized study. SETTING: A primary and tertiary referral centre. PATIENTS: A series of 232 consecutive patients who either had radiological evidence of biliary obstruction or were aged over 70 years were randomly assigned to receive either oral ciprofloxacin or intravenous cefuroxime before and after ERCP. Two-hundred and nine patients finished the study, with 23 being excluded because of withdrawal of consent or incomplete ERCP. INTERVENTIONS: Patients underwent ERCP: blood samples were taken for culture, full blood count and biochemistry before and after the procedure. Clinical follow-up was carried out 7 and 42 days after ERCP. MAIN OUTCOME MEASURES: Clinical, bacteriological or biochemical evidence of cholangitis, septicaemia or adverse drug reactions, and the cost of both protocols. RESULTS: Follow-up was recorded in all 209 patients who completed the study. By 42 days after ERCP, three patients had died (cholangiocancer, pancreatic cancer and renal failure). Cholangitis was diagnosed in one patient from each of the two trial groups. Blood cultures from the patient on ciprofloxacin gave negative results, but a post-ERCP blood sample from the patient on cefuroxime grew Pseudomonas aeruginosa, which was sensitive to ciprofloxacin. There were no serious side-effects in either study group, but two patients assigned to ciprofloxacin became too nauseous to take the medication. The cost of the cefuroxime protocol was l7.56 pounds per patient, compared with 4.76 pounds per patient for the ciprofloxacin protocol. CONCLUSION: A pre- and post-ERCP oral ciprofloxacin regime is safe and provides effective prophylaxis against ERCP-induced cholangitis and septicaemia in high-risk patients. It is also more economical than a regime of intravenous cefuroxime and does not require nursing staff with training in intravenous techniques.